3 | ( | x | − | 2 | ) | + | 1 | = | x | − | ( | 2 | x | − | 1 | ) |
Left side of the equation = | 3 | x | − | 3 | × | 2 | + | 1 |
= | 3 | x | − | 6 | + | 1 |
= | 3 | x | − | 5 |
3 | x | − | 5 | = | x | − | ( | 2 | x | − | 1 | ) |
Right side of the equation = | x | − | 2 | x | + | 1 |
= | - | 1 | x | + | 1 |
3 | x | − | 5 | = | - | 1 | x | + | 1 |
3 | x | + | 1 | x | = | 1 | + | 5 |
4 | x | = | 1 | + | 5 |
4 | x | = | 6 |
x | = | 6 | ÷ | 4 |
= | 6 | × | 1 4 |
= | 3 | × | 1 2 |
x | = | 3 2 |
x | = | 1.5 |